A Novel Splicing Mutation in the FBN2 Gene in a Family With Congenital Contractural Arachnodactyly - Xu, Peiwen; Li, Ruirui; Huang, Sexin; Sun, Menghan; Liu, Jiaolong; Niu, Yuping; Zou, Yang; Li, Jie; Gao, Ming; Li, Xiaolei; Gao, Xuan; Gao, Yuan (Frontiers in Genetics, 2020)
Congenital contractural arachnodactyly (CCA) is an extremely rare monogenic disorder in humans, and the prevalence of CCA is estimated to be less than 1 in 10,000 worldwide. CCA is characterized by arachnodactyly, camptodactyly, the contracture of major joints, scoliosis, pectus deformities, and crumpled ears. Mutations in FBN2 (which encodes fibrillin-2) are responsible for causing this disease. A family with CCA was investigated in this study, and a novel variant, c.3724+3A > C (also identified as IVS28+3A > C), in FBN2 was found in nine patients from the family but was not found in seven unaffected relatives. Reverse transcription-PCR (RT-PCR) and complementary DNA (cDNA) sequencing data showed that exon 28 was skipped in the FBN2 gene. The FBN2 c.3724+3A > C variant led to an in-frame deletion during transcription, which eventually triggered CCA in the Chinese family.